The Prophetic Civilization of Noah: A Study of the Ark, Flood, and Formation of Early Islamic Society Based on Quranic and Biblical Interpretation - Soim, Moh; Shohib, Muhammad; Rosyad, Mohammad Ulil; Munawir, Munawir (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This study investigates the role of Noah in shaping the pillars of Islamic civilisation during the second prophetic period.. By examining the narratives of Noah's life in Islamic sources, the study identifies the key pillars that shaped the Islamic civilisation of the period. The main focus involves analysing aspects of Noah's prophethood, da'wah, people, flood, ship and its scientific evidence. The method used was qualitative and the data sources were obtained through observations in several books and verses and interpretations of the Qur'an. Then, it was analysed using some of the literature of exegetes and the opinions of scientists. The findings are as follows. First, the existence of the civilisation of the Prophet Noah (peace be upon him) is currently being researched. Second, household civilisation in addressing existing conflicts is extraordinary. Third, the social civilisation that was built by preaching to all its people with patience and nobleness owned by Noah As. Fourth, the civilisation of the largest ship architecture at that time and can load many people, animals and storm-proof quality with a long duration.